Actinomycete biodiversity assessed by culture-based and metagenomic investigations of three distinct samples in Cape Town, South Africa - Davids, Muhammad Saeed (Department of Molecular and Cell Biology, 2014)
All of the samples used for actinobacterial isolation were subjected to a culture-independent (metagenomic) study. The results provided an explanation for why no actinomycetes were found in the aquatic samples, as all of the sequenced clones were shown to be most closely related to uncultured bacteria. In the terrestrial sample, a total of 120 clones were obtained and all were sent for sequencing.